Chemotherapy-induced adverse drug reactions in oncology patients: A prospective observational survey - Deepti Chopra; Harmeet S Rehan; Vibha Sharma; Ritu Mishra (Indian Journal of Medical and Paediatric Oncology)
Background: Chemotherapy, a multimodal approach to oncological treatment, involves highly complex regimens and hence accounts to high susceptibility toward adverse drug reactions (ADRs). The present study aims to determine the prevalence of adverse events in patients treated with chemotherapy. Materials and Methods: Spontaneous ADR report of patients on antineoplastic drugs received in the past 2 years (January 2011-January 2013) were studied. These reports were analyzed for various carcinomas under treatment, medications used, types of ADRs, organ system involvement, severity, causality assessment, and preventability. Results: Over a period of 2 years, a total 591 cases were received with an incidence of 58.6%. The prevalence of ADRs was more in female patients (73.6%) as compared to men. ADRs mostly occurred in the age group of 41-50 years (27.4%). Patients treated for breast carcinoma (39.1%) reported the highest incidence of ADRs. Cisplatin (19.6%) was found to be the most common offending drug. The most common ADR reported was nausea and vomiting (23%). Gastroenterology (40.1%) was the most affected system. About 50.2% of the ADRs required treatment and 12.9% ADRs were considered serious. Causality assessment revealed that 80% of the ADRs were possible. About 86.97% cases were found to be mild, and 51% were not preventable. Conclusion: The success of chemotherapy comes with the word of caution regarding toxicities of antineoplastic drugs. Pharmacovigilance of these drugs needs to be explored, and use of preventative measures needs to be enhanced in order to reduce the incidence and severity of ADRs.